Comparative analysis of the conditions of living in lower silesian districts over the period of 2010-2015 - Safin, Krzysztof; Błaczkowska, Anna; Franków, Marzena; Rólczyński, Tomasz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of the paper is to analyze variation in quality of life across Lower Silesia, taking into account the disparities within individual districts. At the beginning a theoretical analysis of the measurement quality of life based on available literature was made. In the next step based on the data covering the years 2010-2015, a statistical comparative analysis of the living situation in Lower Silesian districts was conducted which aim was to identify the key factors which would describe the similarities and differences in terms of quality of life among the Lower Silesian population. In the research were used data from the Local Databank, Central Statistical Office and from a survey. The analyzes used objective and subjective measures of quality of life. Research methods were also subjective and objective. Expert methods and selected methods of multidimensional comparative analysis–weighted standardized sums method were used
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 483, s. 136-151
Keywords: quality of life; statistical methods; comparative analysis; jakość życia; metody statystyczne; analiza porównawcza